Celebrity Credibility, Social Media Influence, and Purchase Intention: The Mediating Role of Trustworthiness and Perceived Quality on Kopi Kenangan Instagram - Bunga Salsabila; Elvira Azis (Journal of Business, Social and Technology, 2026)
Background: The Indonesian coffee beverage industry continues to grow, particularly among young consumers who are active on social media. Through Instagram, Kopi Kenangan collaborates with celebrities and influencers to strengthen brand image, build trust, and increase purchase intention. However, negative public perceptions of celebrity endorsers may reduce trust, perceived quality, and consumers’ willingness to buy. Objective: This study aims to analyze the influence of celebrity credibility, celebrity attractiveness, and social media influence on trustworthiness, perceived quality, and purchase intention toward Kopi Kenangan products on Instagram. Methods: This study used a quantitative survey approach with non-probability sampling. Data from 385 respondents were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The measurement model met reliability and validity criteria, with all outer loadings above 0.708, Composite Reliability values above 0.70, AVE values above 0.50, and HTMT values below 0.85. Results: The findings showed that social media influence (β = 0.565, p < 0.001) and celebrity credibility (β = 0.308, p < 0.001) significantly influenced trustworthiness, while celebrity attractiveness had no significant effect. Perceived quality was strongly influenced by social media influence (β = 0.762, p < 0.001) and significantly affected purchase intention (β = 0.556, p < 0.001). Trustworthiness also significantly influenced purchase intention (β = 0.151, p = 0.035). Conclusion: Purchase intention toward Kopi Kenangan is more effectively increased through perceived quality and trust, driven mainly by social media influence and celebrity credibility rather than celebrity attractiveness.